An Analysis of Financial Ratios in The Health Service Industry Listed on The Indonesia Stock Exchange Before and Durin The Covid-19 Pandemic (INTEGRATION PROCEEDING, 2023)
The Covid-19 pandemic has had an impact on the health and economy of Indonesia, many companies are experiencing financial difficulties. Where these financial difficulties can be done early prevention by analyzing financial reports and evaluating financial performance. Research purposes to find out the financial performance of the health service industry listed on the Indonesian Stock Exchange before and during the Covid-19 pandemic. This study used a quantitative method with a total sample of 7 companies with a purposive sampling technique and the results of the financial ratio for total asset turnover before 0.545 and during the pandemic were 0,57, the results for the current ratio before 2.77 and during the pandemic were 2.32, the results for the debt to asset ratio before 0.28 and during the pandemic were 0.31 and the return on investment before 0.033 and during the pandemic 0.68. The company's financial performance has improved from before the covid-19 to the time of the covid-19 pandemic.